Analisis Karakteristik dan Potensi Lahan Pekarangan untuk Mendukung Penganekaragaman Konsumsi Pangan Keluarga di Kecamatan Kepil Kabupaten Wonosobo - Mindasa, Mindasa (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2025)
The potential of the yard contributes to food availability and diversification of food consumption. Utilization for agricultural activities will provide benefits in the form of the availability of healthy and nutritious fresh food. This study aims to analyze the characteristics and potential of yard land based on supporting the diversification of family food consumption in Kepil District. This study was conducted in Kepil District from March to June 2025. The study was conducted using a survey method, sampling with stratified random sampling. The results showed that the majority of yard land was in the narrow category with a dominance of the front zone for cultivating vegetables and spices. A total of 10 types of plants that are often found in more than 50% of yards in Kepil District are; red cayenne pepper, curly chili, spring onions, eggplant, tomatoes, celery, caisim, ginger, turmeric and lemongrass. Food diversification in Kepil District found 5 groups of fresh food from plants 5 types of cereal group food, 26 types of vegetable group food, 14 types of spice group food, 22 types of fruit group food, 1 type of freshener and sweetener group food, 1 type of poultry group food, 3 types of mammalian animal product group food, 3 types of fish group food. The pattern of utilization of food sources in the yard of Kepil District is as a source of carbohydrates 5.33%, fat 4.00%, minerals 49.33%, protein 9.33% and vitamins 32.00%.